Distribution properties of airflow in the full envelope type maize stalk chopping chamber - Liu, Peng; He, Jin; Yu, Changchang; Lou, Shangyi; Wang, Chunlei; Wang, Mingxu; Shen, Huipeng (International Journal of Agricultural and Biological Engineering, 2024)
Chopped and spread maize stalks improve soil structure and fertility. However, because of the research absence of airflow distribution in the chopping chamber, improving spreading uniformity of chopped stalks was limited. Therefore, in this study, computational fluid dynamics (CFD) technology was applied to analyze the influence of structural and operational parameters of chopping and spreading machine on the velocity, pressure, and turbulent kinetic energy distribution of airflow in the chopping chamber. The experimental factors considered were the relative position angle between the collecting-chopping shaft and the sliding-supporting shaft (RPA), working velocity (WV) of the chopping chamber and rotational velocity of the collecting-chopping blade (RVCCB). The results revealed that RPA and RVCCB had a significant influence on the maximum negative pressure in the inlet (MNPI), the proportion of negative pressure area at inlet (PNPAI), and the maximum pressure drop at inlet and outlet (MPDIO). Additionally, RVCCB had a strong influence on the maximum velocity, average velocity and velocity variation coefficient of airflow at the outlet. Moreover, maximum turbulence (MT) and maximum turbulent kinetic energy dissipation rate (MTKEDR) showed a positive relationship with RVCCB. To determine the values of RPA, RVCCB, and WV, a multivariate parameters optimization regression model was constructed, which yielded the optimal values of 15°, 1800 r/min, and 0.50 m/s, respectively. Subsequently, a hyperbolic spiral type guiding shell with an arc length of 90° was designed to enhance the uniform distribution of airflow in the chopping chamber. Finally, a validation experiment of airflow distribution was conducted. The results showed that the velocity difference between the simulation and the validation experiment was less than 15%, indicating the accuracy of CFD simulation, and the spreading uniformities of the chopped stalks were better than national standards. The findings can serve as technical and theoretical support for the design and optimization of chopping and spreading machines. Keywords: maize stalk retention, conservation tillage, spreading process, airflow distribution, full envelope type chopping chamber DOI: 10.25165/j.ijabe.20241705.8561 Citation: Liu P, He J, Yu C C, Lou S Y, Wang C L, Wang M X, et al. Distribution properties of airflow in the full envelope type maize stalk chopping chamber. Int J Agric & Biol Eng, 2024; 17(5): 137-150.